Pembuatan Sistem Absensi Siswa Praktek Kerja Lapangan (PKL) Berbasis Web di CV Sae Akademi Digital Medan - Syuhada, Rahmad; Muhathir, Muhathir (INCODING: Journal of Informatics and Computer Science Engineering, 2024)
The manual attendance system used in CV SAE Akademi Digital Medan in recording the attendance of Field Work Practice (PKL) students has several shortcomings, such as lack of efficiency, vulnerability to recording errors, and difficulty in real-time monitoring. This research aims to design and implement a more modern and efficient web-based attendance system. The research methods used include needs analysis, system design, development, implementation, and testing. The system is designed using photo upload technology to validate student attendance based on time and location digitally. The study results show that this web-based attendance system has succeeded in increasing the efficiency, accuracy, and transparency of student attendance management. In addition, the dashboard monitoring feature makes it easier for supervisors to monitor student attendance in real time. This system is expected to not only be a solution for CV SAE Digital Academy Medan but also a model for implementing a modern attendance system in other educational institutions.